Green Tea Attenuates Experimental Hepatitis in Context of Oxidative Stress - Jihan Hussein, Eman Refaat, Safaa Morsy, Dalia Medhat and Fatma Oraby (Journal of Applied Pharmaceutical Science, 2013)
Food derived antioxidants have a strong potential for long term use as chemo-preventive agents in disease states involving oxidative stress such as tea. This study was done to clarify the potential effect of green tea extract in protecting the liver from lipopolysaccharide (LPS)-induced hepatitis in D-galactosamine (D-GalN) sensitized rats. Forty male albino rats weighing 180 - 200 g were divided into four groups; group I : healthy rats received vehicle only , group II :healthy rats received green tea (GT) extract orally for thirty days , Group III: healthy rats received vehicle only before induction of hepatitis. Group IV: healthy rats received green tea extract orally for thirty days before induction of hepatitis. After the experimental period, serum liver enzymes and liver oxidant /antioxidant profile were determined. Liver coenzymeQ10 (CoQ10) was estimated by HPLC method using C18 column and UV detector at 275 nm. The current date appeared the effective role of green tea extract in protecting the liver against the injury induced by D-GalN/LPS which may be attributed to polyphenolic compounds that scavenge a wide range of free radicals and increasing the antioxidant enzymes.
Keywords: Experimental hepatitis,paraoxonase, coenzyme Q10, HPLC, oxidative stress, green tea.